1995
DOI: 10.1111/j.1399-6576.1995.tb04175.x
|View full text |Cite
|
Sign up to set email alerts
|

QT interval of the ECG, heart rate and arterial pressure during anaesthetic induction: comparative effects of alfentanil and esmolol

Abstract: In a double-blind study the effect of esmolol and alfentanil on the QT interval of the ECG corrected by the heart rate (QTc), heart rate and arterial pressure during anaesthetic induction was studied in 59 oxycodone- and atropine-premedicated ASA class I-(II) patients with a mean age of 26 yr (range 15-50 yr). The patients were randomly allocated to one of the four groups: saline, esmolol 2 mg.kg-1, esmolol 3 mg.kg-1 or alfentanil 0.03 mg.kg-1. Both doses of esmolol prevented the prolongation of the QTc interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 17 publications
2
48
1
1
Order By: Relevance
“…Generally, it is known that tracheal intubation during induction stimulates sympathetic activity, which, as a result, prolongs the QTc interval [15,16]. In contrast, other studies have shown the opposite, with tracheal intubation decreasing the QTc interval [17].…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Generally, it is known that tracheal intubation during induction stimulates sympathetic activity, which, as a result, prolongs the QTc interval [15,16]. In contrast, other studies have shown the opposite, with tracheal intubation decreasing the QTc interval [17].…”
mentioning
confidence: 72%
“…In the case of opioids, their influence on the QTc interval and its generation is unclear [7,17]. Moreover, it has been found that alfentanil does not prolong the QTc interval during intubation [24] and also that alfentanil cannot prevent QTc prolongation [16]. Therefore, it is difficult to conclude that sympathetic activity is the main trigger of QTc interval prolongation during tracheal intubation.…”
Section: ó 2008 the Authorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Rapid injection of catecholamine, brief stimulation of the sympathetic nervous system, and an imbalance of the cardiac sympathetic tone cause prolongation of the QTc interval [15][16][17][18], which may be related to sympathetic stimulation. However, Korpinen et al [10] reported that b-blockers did not attenuate the QTc prolongation during induction of anaesthesia. The effect of opioids on the prolongation of the QTc interval during induction is unclear [13,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of a potent opioid or b-adrenergic blockade is generally recommended to attenuate sympathoadrenal responses to laryngoscopy and intubation. However, it has been reported that b-blockers may not attenuate QTc prolongation during the induction of anaesthesia [9,10]. Studies concerning the effects of alfentanil on preventing the prolongation of the QTc interval following intubation are not consistent, depending on different premedication or patient ages [10,11].…”
mentioning
confidence: 93%